Postsecondary writing studies in Hispanic Latin America: Intertextual dynamics and intellectual influence (UCL Press, 2017)
As texts enact historically situated ways of making knowledge, intertextual analysis through citation patterns can shed some light on a community's epistemologies. The present research seeks a deeper understanding of the theoretical trends, the influences, and the emerging disciplinary configuration of the writing studies community in Latin America. Findings confirm the existence of an extremely diverse theoretical landscape, with a strong influence of Englishspeaking authors, followed by locals. A network analysis model for co-cited authors reveals two well-differentiated approaches. This kind of analysis constitutes a useful input to further the discussion about disciplinary epistemologies and ideologies of the field in the region.